Haematological and biochemical analysis of broiler chickens fed chitin and chitosan isolated from cricket and shrimp - Ibitoye, Emmanuel Busayo; Idris, Lokman Hakim; Mohd Noor, Mohd Hezmee; Goh, Yong Meng; Abu Bakar @ Zakaria, Md Zuki (Faculty of Veterinary Medicine, Universiti Putra Malaysia, 2018)
Dietary components can affect haematological and serum biochemical indices which dictates health status. Chitin and chitosan are known feed additives. Due to paucity of information, this study aims at comparing the effect of cricket and shrimp chitin and chitosan on the haematology and serum biochemistry of broilers. 150 days old Cobb broiler chicks were randomly fed one of the five dietary treatments. Birds in treatment: T1 only basal diet (control); T2, T3, T4 and T5 basal diet+0.5g cricket chitin, cricket chitosan, shrimp chitin and shrimp chitosan/kg diet respectively. It was observed that cricket chitin and chitosan did not (p>0.05) affect the haematology and serum biochemistry, but they reduce serum cholesterol (chol) and triglycerides (trigl), hence they may have a beneficial effect on growth and as hypolipidaemic agent. Although cricket chitin appears to be more effective as a hypolipidaemic agent. Also, cricket or shrimp chitin and chitosan did not vary significantly (p>0.05) regarding blood and serum chemistry. Cricket chitin and chitosan, based on this study are potential feed additives and can substitute commercial chitin and chitosan in broiler production.